(untitled) (مجلة الواحات للبحوث والدراسات, 2020)
Since the development of F. Modigliani and M. Miller’s theorem (1958-1963), the financial literature has been abundant with works dealing with the impact of financing policy on value of the company. It is within this framework that the objective of this research falls, by posing the following problematic: Is debt a means of adjusting financial resources to the need for financing or on the contrary a source of creation valuable?